2015
DOI: 10.1155/2015/547473
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Increases Beta-Catenin Level through Protein Kinase A Activation and Regulates OPG Expression in Rat Primary Osteoblasts

Abstract: Ghrelin, by binding growth hormone secretagogue receptor (GHS-R), promotes osteoblast proliferation but the signaling mechanism of GHS-R on these cells remains unclear. Since canonical Wnt/β-catenin pathway is critically associated with bone homeostasis, we investigated its involvement in mediating ghrelin effects in osteoblasts and in osteoblast-osteoclast cross talk. Ghrelin (10−10M) significantly increased β-catenin levels in rat osteoblasts (rOB). This stimulatory action on β-catenin involves a specific in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
0
9
0
1
Order By: Relevance
“…[97][98][99] By acting on its receptor, ghrelin was also shown to stimulate osteoprotegerin (OPG) gene expression, which inhibits the coupling between the OC and OB, leading to reduced OB-related OC differentiation. 100 Other studies found that ghrelin inhibited apoptosis in mouse preosteoblastic MC3T3-E1 cells induced by serum starvation in a mechanism also mediated by GHSR/ERK and GHSR/PI3K/AKT pathways. 101 r AMSO, CORNISH, AND BRIMBLE The effect of ghrelin on bone cannot entirely be ascribed to its GH-releasing activity as infusion of ghrelin increased BMD in genetically GH-deficient dwarf rats, indicating a direct, GH-independent effect on bone metabolism.…”
Section: A Ghrelinmentioning
confidence: 96%
See 1 more Smart Citation
“…[97][98][99] By acting on its receptor, ghrelin was also shown to stimulate osteoprotegerin (OPG) gene expression, which inhibits the coupling between the OC and OB, leading to reduced OB-related OC differentiation. 100 Other studies found that ghrelin inhibited apoptosis in mouse preosteoblastic MC3T3-E1 cells induced by serum starvation in a mechanism also mediated by GHSR/ERK and GHSR/PI3K/AKT pathways. 101 r AMSO, CORNISH, AND BRIMBLE The effect of ghrelin on bone cannot entirely be ascribed to its GH-releasing activity as infusion of ghrelin increased BMD in genetically GH-deficient dwarf rats, indicating a direct, GH-independent effect on bone metabolism.…”
Section: A Ghrelinmentioning
confidence: 96%
“…It was shown that ghrelin stimulates proliferation in various cell types through mitogen‐activated protein kinase (MAPK)/ERK and phosphoinositide 3‐kinase (PI3K)/AKT pathways by acting on GHSR . By acting on its receptor, ghrelin was also shown to stimulate osteoprotegerin (OPG) gene expression, which inhibits the coupling between the OC and OB, leading to reduced OB‐related OC differentiation . Other studies found that ghrelin inhibited apoptosis in mouse preosteoblastic MC3T3‐E1 cells induced by serum starvation in a mechanism also mediated by GHSR/ERK and GHSR/PI3K/AKT pathways …”
Section: Growth Hormone (Gh) Releasing Peptidesmentioning
confidence: 99%
“…It is well known that cells of the osteoblastic lineage exert a physiological control of osteoclast formation and activity [27,28] which involves both the osteoclast stimulus Receptor Activator of NFB Ligand (RANKL) and inhibition of this by the decoy receptor osteoprotegerin (OPG). Since, under stress conditions, RANKL levels exceed OPG production [29], we evaluated whether or not D3R might modulate the expression of OPG/RANKL mRNA in MC3T3-E1 cells.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the general view has been that the link between Wnt signalling and metabolism is mediated by transcriptional targets of Wnt signalling, although other cross-talk mechanisms are possible (as reviewed by [ 40 ]). There is suggestive evidence that ghrelin could boost Wnt signalling [ [41] , [42] , [43] ], although the exact mechanisms have not been clearly defined. It is conceivable that in some circumstances, ghrelin could outcompete Wnt as a substrate for Notum, unleashing increased Wnt signalling.…”
Section: Discussionmentioning
confidence: 99%